Fear of unintended pregnancy and sexual quality of life during the menopausal transition in a Turkish population: A cross-sectional study of associated factors - Aysun Badem (PLoS ONE, 2026)
Objective This study aimed to investigate fear of unintended pregnancy, contraceptive method use, sexual quality of life, and associated factors among perimenopausal women. Methods This descriptive cross-sectional study was conducted in 2025 with 124 perimenopausal women aged 40–50 years. The data have been collected using a sociodemographic-obstetric questionnaire and the Turkish version of the Sexual Quality of Life-Female (SQOL-F) scale. Mann–Whitney U, Kruskal–Wallis H and Linear regression analysis tests were applied. Results The median SQOL-F score was 84.50. The score indicated a moderate-to-high level of sexual quality of life. Significant differences in SQOL-F scores were observed according to employment status, education level, parity, mode of delivery, childbirth experience, and fear of unintended pregnancy (p < 0.05). Relatively higher SQOL-F scores have been exposed by women with higher education levels, lower parity, cesarean delivery, and positive birth experiences. Significantly lower SQOL-F scores have been observed on the fear of unintended pregnancy predicated women. Conclusions The fear of unintended pregnancy is prevalent among perimenopausal women and is associated with lower sexual quality of life. Comprehensive nursing interventions may be critical including contraceptive counseling and sexual health education tailored to the needs of perimenopausal women.